Black Hat physical device security exploiting hardware and software - Miller, Drew, 1978- (Rockland, MA : Syngress ; [Sebastopol, CA] : Distributed by O'Reilly in the United States and Canada, 2005)
Black Hat, Inc. is the premier, worldwide provider of security training, consulting, and conferences. In this book the Black Hat experts show readers the types of attacks that can be done to physical devices such as motion detectors, video monitoring and closed circuit systems, authentication systems, thumbprint and voice print devices, retina scans, and more. The Black Hat Briefings held every year in Las Vegas, Washington DC, Amsterdam, and Singapore continually expose the greatest threats to cyber security and provide IT mind leaders with ground breaking defensive techniques. There are no books that show security and networking professionals how to protect physical security devices. This unique book provides step-by-step instructions for assessing the vulnerability of a security device such as a retina scanner, seeing how it might be compromised, and taking protective measures. The book covers the actual device as well as the software that runs it. By way of example, a thumbprint scanner that allows the thumbprint to remain on the glass from the last person could be bypassed by pressing a "gummy bear" piece of candy against the glass so that the scan works against the last thumbprint that was used on the device. This is a simple example of an attack against a physical authentication system. * First book by world-renowned Black Hat, Inc. security consultants and trainers * First book that details methods for attacking and defending physical security devices * Black Hat, Inc. is the premier, worldwide provider of security training, consulting, and conferences.
The enveloping paradigm -- Inheriting security problems -- Information security -- Mitigating exposures -- Monitoring software exposures -- Taking a hard look at hardware -- Authenticating people -- Monitoring and detecting deviations -- Notifying systems.
Includes index.
Keywords: Computer networks -- Access control -- Handbooks, manuals, etc; Computer networks -- Security measures -- Handbooks, manuals, etc; Computer security -- Handbooks, manuals, etc; Computer crimes; Electronic books; Handbooks, manuals, etc